Home Industry Furniture in Surabaya: Condition and Their Needs - Helena Sidharta; Christina Yanita Setyawati; Chatarina Felisia (Junal Ilmu Manajemen, 2022)
Home industry Furniture in Surabaya, Indonesia, at the micro and small business level. Like other developing countries, micro, small, and medium enterprises have an essential role in economic growth. The problem is that imported products make them suffer. They try to sustain in this tough competition. This study aims to understand their position and what they need to sustain or grow in the future. This study uses a qualitative approach with interviews as the primary data source, surveys and documentation as supporting data sources. The respondent in this study, both for interview and survey, is the owner of the home industry, with a minimum of ten years in business and the level micro and small business. The result of this study shows that home industry' owner must change their mindset about how they do their business significantly; they must innovate their product, have a new idea, have a professional marketing plan, and the important one is to understand the market.